Differential diagnosis of otitis media with effusion using label-free Raman spectroscopy: A pilot study - Pandey, Rishikesh (J Biophotonics, 2018)
Otitis media with effusion (OME) is an important and common condition affecting hearing in pediatric patients characterized by the presence of fluid in the middle ear space. The fluid is normally described as serous or mucoid based on differences in the fluid viscosity. The differential diagnosis of two OMEs, namely serous and mucoid is of significant clinical value because while the former is self-limiting, surgical procedure is commonly required for the latter. However, accurate identification of fluid types remains a challenging target unattainable with current clinical modalities due to unavailability of nonperturbative molecular tools. Here, we report an emerging spectroscopy approach featuring Raman scattering and multivariate analysis of spectral patterns to discern serous and mucoid fluids, obtained from pediatric patients undergoing myringotomy and tube placement, by providing information of differentially expressed molecules with high specificity. We demonstrate the feasibility of Raman spectroscopy-based approach to categorize middle ear effusion based on the characteristic spectral markers, notably of mucin, with classification accuracy of 91% and 93% for serous and mucoid, respectively. Our findings pave the way for further development of such a tool for fully noninvasive application that will lead to objective and accurate diagnosis thereby reducing unnecessary visits and surgical procedures.